Evaluation of RNA extraction procedure for drought gene expression in basmati rice - YADAV, ASHWANI; SHARMA, ANUBHUTI; KUMAR, ASHWANI; YADAV, RENU; KUMAR, RAJENDRA (The Indian Journal of Agricultural Sciences, 2021)
Basmati rice contains large amounts of polysaccharides and polyphenols. Due to these compounds, isolation of superior quality RNA from rice tissue is complicated. Most of the published procedures failed to yield adequate quantity of high-quality RNA from various rice tissues appropriate for gene expression studies. We conducted experiments and observed as the average ratio at A260/280 of basmati rice leave derived RNA extracted through the phenol-SDS procedure ranging from 1.64 to 1.70, which indicated that the samples contained protein contamination and were low in purity. On the other hand, in our modified protocol typical yields of RNA for the four Basmati rice genotypes ranged from 35-50 μg. The A260/280 ratio ranged from 1.95-2.11 for all the samples and indicated that the RNA is of high quality free from impurities like polysaccharides and polyphenols contaminations. Thus, the quality RNA with high yield from rice leaves or may be other plant tissues having high concentration of impurities like polyphenols and polysaccharides may be extracted and purified by this modified protocol can be used for various downstream applications including RNA-seq, RT-PCR and qPCR.